Seventh IEEE International Conference on E-Commerce Technology (CEC'05)
DOI: 10.1109/icect.2005.4
|View full text |Cite
|
Sign up to set email alerts
|

A Fuzzy Trust Model for E-Commerce

Abstract: Abstract:Although, there are many successful E-commerce organizations, it is argued that E-commerce has not reached its full potential. Trust was often cited as the main reason as many customers are still skeptical about some online vendors. Many trust models have been developed, but most are subjective and did not take into account the vagueness and ambiguity of the domain and the specificity of customers. We have developed a model that attempts to identify the information customers expect to find on a vendor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…For instances, Grandison and Sloman [6] define trust as a quantified belief by a truster with respect to the competence, honesty, security and dependability of a trustee within a specified context. The model given by Nefti et al [16] considers some kind of information on a merchant website that is shown to increase customer trust. Abdul-Rahman and Hailes [1] make use of four degrees of belief to typify agent trustworthiness: vt (very trustworthy), t (trustworthy), u (untrustworthy) and vu (very untrustworthy).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For instances, Grandison and Sloman [6] define trust as a quantified belief by a truster with respect to the competence, honesty, security and dependability of a trustee within a specified context. The model given by Nefti et al [16] considers some kind of information on a merchant website that is shown to increase customer trust. Abdul-Rahman and Hailes [1] make use of four degrees of belief to typify agent trustworthiness: vt (very trustworthy), t (trustworthy), u (untrustworthy) and vu (very untrustworthy).…”
Section: Related Workmentioning
confidence: 99%
“…Many models of computational trust for multiagent systems have been proposed such as Grandison and Sloman [6], Nefti et al [16], Yu and Singh [30][31][32], Sen and Sajja's [26], Carter et al [4], Ramchurn et al [22], Huynh et al [12,13], Victor et al [28], Nguyen and Tran [17][18][19], Katz and Golbeck [14], Hang et al [8], Guha et al [7], Vogiatzis et al [29]. Most of such models are based on two sources of information.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it is " a mental state comprising expectancy (the trustor expects a specific behavior from the trustee) and belief" [3]. Computational trust models have recently been drawing the attention of many scientific communities from various disciplines [6], [7] to analyze interpersonal or inter-organizational trust in different domains such as e-commerce [8] and social web applications [9].…”
Section: Introductionmentioning
confidence: 99%
“…29 | P a g e www.ijarai.thesai.org [4] Guha et al [9] Hang et al [10] Hermoso et al [11] Jennings et al [12], [13] Katz and Golbeck [16] Lashkari et al [17] Li and Gui [18] Manchala [19] Nefti et al [20] Nguyen and Tran [22], [23] Ramchurn et al [24] Sabater and Sierra [26], [27] Schillo et al [28] Sen and Sajja's [29] Shibata et al [30] Singh and colleagues [36], [37] Teacy et al [31], [32] Victor et al [33] Vogiatzis et al [34] Whitby et al [35] Zhang, Robin and collegues [39], [14], [5], [6] Our model…”
Section: Computational Model Of Trustmentioning
confidence: 99%
“…Firstly, The models are based on personal experiences that a truster has on some trustee after their transactions performed in the past. For instance, Manchala [19] and Nefti et al [20] proposed models for the trust measure in e-commerce based on fuzzy computation with parameters such as cost of a transaction, transaction history, customer loyalty, indemnity and spending patterns. The probability theory-based model of Schillo et al [28] is intended for scenarios where the result of an interaction between two agents is a boolean impression such as good or bad but without degrees of satisfaction.…”
Section: Related Workmentioning
confidence: 99%